ANALISIS PERMINTAAN TERHADAP IKAN BUDIDAYA KONSUMSI DI KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Trian Zulhadi (Berkala Perikanan Terubuk, 2010)
This study aimed to find out factors influencing the demand ofconsumption of aqua culture in Singingi Hilir district, the Regency of KuantanSingingi. There are eight parameters in this study, namely kinds of fish offered,sales frequency, the number of fish sold in kilograms, the way to obtain the fish,the level of income, desire, and price. Data used are both primary and secondary.The descriptive method was used to analyze the data. The number of therespondents was 531. The research findings show that the interest of the people inthe district in consuming aqua culture is higher than freshwater fish so that thedemand of aqua culture fish in Singingi Hilir district is highly potential toimprove the welfare of the farmers in particular, and the people in Singingi Hilirdistrict in general.